A new microemulsion approach for producing molecularly imprinted polymers with selective recognition cavities for gallic acid. Issue 6 (9th October 2012) - Nicolescu, Tanta V.; Meouche, Walid; Branger, Catherine; Margaillan, André; Sarbu, Andrei; Fruth, Victor; Donescu, Dan
Abstract: Bulk and microemulsion systems were studied in order to obtain molecularly imprinted copolymers selective for gallic acid. Both systems contained acrylic acid as the functional monomer and ethylene glycol dimethacrylate as crosslinker. Microemulsion formation was confirmed by refractive index measurements and by conductivity analyses. Simple uptake tests revealed higher affinities for the microemulsion polymers; a 3.55 imprinting factor and a 0.275 g gallic acid (g polymer) –1 adsorption capacity were recorded. Competitive uptake tests, from an oak bark extract, were in agreement with the simple uptake results and BET analyses. Microemulsion polymer particles selectively bind 4.58 times more gallic acid molecules relative to other competitor species. Abstract : "Freezing" the bicontinuous structure, by crosslinking, leads to a very porous structure, providing an easier diffusion of gallic acid molecules within the particles.